Zapis aleatoryzmu kontrolowanego jako instrukcja działania dla wykonawców na wybranych przykładach kompozycji Witolda Lutosławskiego. - Chrenowicz, Jakub (Investigationes Linguisticae, 2018)
The goal of the article is to present the transcription system in Witold Lutosławski’s pieces composed using the technique of controlled aleatorism as a formal language for the transmission of instructions to the conductor and orchestra musicians performing those works. The starting point for my ruminations is to explore controlled aleatorism from the performer’s perspective.The text invokes excerpts from three pieces by Witold Lutosławski: Cello concerto, Chain I, and Piano Concerto. The author presents an account of the controlled aleatorism technique and analyzes the graphic signs used in the aforementioned compositions, along with the ways in which they are interpreted by performers. The author contends that the examined transcriptions are a collection of instructions of varying degrees of complexity, addressed to musicians performing the analyzed pieces. Such a system of notation can be interpreted as a formal language which the composer programmed the work of the conductor and orchestra musicians. Beginning with the simplest instructions, he proceeded to create complex, algorithmic commands.The conclusions drawn from the above analyses point to the essence of controlled aleatorism in music notation and its interpretations. The element of control overrides the element of randomness, and such a state of affairs is attained by using a particular type of transcription.